CFD Analysis of Energy Separation in Ranque-Hilsch Vortex Tube at Cryogenic Temperature. (14th November 2013) - Dutta, T.; Sinhamahapatra, K. P.; Bandyopadhyay, S. S.
Abstract : Study of the energy separation phenomenon in vortex tube (VT) at cryogenic temperature (temperature range below 123 K) has become important because of the potential application of VT as in-flight air separator in air breathing propulsion. In the present study, a CFD model is used to simulate the energy separation phenomenon in VT with gaseous air at cryogenic temperature as working fluid. Energy separation at cryogenic temperature is found to be considerably less than that obtained at normal atmospheric temperature due to lower values of inlet enthalpy and velocity. Transfer of tangential shear work from inner to outer fluid layers is found to be the cause of energy separation. A parametric sensitivity analysis is carried out in order to optimize the energy separation at cryogenic temperature. Also, rates of energy transfer in the form of sensible heat and shear work in radial and axial directions are calculated to investigate the possible explanation of the variation of the hot and cold outlet temperatures with respect to various geometric and physical input parameters.